Psycho-physical perfection of economic specialties' girl students under influence of sport-oriented technology, based on prevalence of volleyball practicing - I.O. Salatenko; O.Ya. Dubinskaya (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to work out content of sport-oriented technology of physical education, based on prevalence of volleyball practicing. Material: in the research two experimental (n=25, n=25) and one control (n=25) groups of girl students participated. The content of sport-oriented technology, based on prevalence of volleyball practicing included additionally elements of fitness. студенток. Quickness of mental processes and efficiency of mind operations were assessed with the help of special cards, on which 9 dials with pointers were depicted. The sense of test was: addition of dials' readings in mind; simultaneous calculation of value of scale one division; keeping in memory the previous sum of readings. This task was to be fulfilled for 6 minutes. Results: it was found that quickness of mental processes and mind operations as well as operative memory were at level below average. The most expressed positive factor was registered in group in which circle sport trainings were conducted. It was also found that over-fatigue at the end of academic year influences on testing indicators. Conclusions: the offered by us sport-oriented technology, based on prevalence of volleyball practicing can be recommended as effective mean of economic specialties girl students' psycho-physical qualities' strengthening.